2009
DOI: 10.1007/978-3-642-03655-2_27
|View full text |Cite
|
Sign up to set email alerts
|

Considering Cost in Usability Evaluation of Mobile Applications: Who, Where and When

Abstract: Abstract. As computing moves from desktop to outdoor everyday life activities, usability evaluation must take into account new aspects, related with mobility and space. In this paper the effectiveness of established usability evaluation methods is examined through an extensive case study. The usability of an educational mobile museum application was tested using three different methods: inspection by experts, use in lab setting and use in the field. Results indicate that each method uncovers different types of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Specifically, this study was performed as a "laboratory evaluation," a very common technique [51] which is widely applied (47% alone, and 10% in combination with field studies) [52] and, in addition, it is three times less cost consuming than field evaluations [53]. The downside of laboratory evaluations is its lack of context (in terms of real usage and environmental influences) [53,54], only present in nearly 11% of the studies [52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, this study was performed as a "laboratory evaluation," a very common technique [51] which is widely applied (47% alone, and 10% in combination with field studies) [52] and, in addition, it is three times less cost consuming than field evaluations [53]. The downside of laboratory evaluations is its lack of context (in terms of real usage and environmental influences) [53,54], only present in nearly 11% of the studies [52].…”
Section: Discussionmentioning
confidence: 99%
“…The downside of laboratory evaluations is its lack of context (in terms of real usage and environmental influences) [53,54], only present in nearly 11% of the studies [52].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies conclude that field studies and field evaluations are time-consuming and costly [18,26,30]. Kaikkonen et al report that studies showed that usability field-testing required double the time compared their lab testing [30], while Jambon et al found that their field tests required almost triple the time compared to lab tests [26].…”
Section: Social Network and Input And Interactionmentioning
confidence: 99%
“…Several studies, for example [5,18,19,26,30,47], find that properly conducted lab usability evaluations can identify many of the usability issues (i.e. usability problems) identified in field evaluations.…”
Section: Social Network and Input And Interactionmentioning
confidence: 99%
See 1 more Smart Citation